Phytochemical Analysis and In-vitro Antimicrobial Activity of Acacia seyal Methanolic Leaf Extract - Mustafa, Ahmed A.; Kabbashi, Ahmed S.; Keshar, Ahlam M.; Abdrabo, Amel M.; Mohammed, Wahaj M. (Gezira Journal of Engineering and Applied Sciences; Vol 18 No 1 (2023), 2026)
This preliminary study aimed to evaluate the antimicrobial potential and phytochemical profile of methanolic leaf extract derived from Acacia seyal . Qualitative phytochemical screening was conducted using standard test tube methods to identify the major secondary metabolite classes. The in-vitro antimicrobial activity was assessed against a panel of clinically relevant pathogens, including Escherichia coli , Staphylococcus aureus , Pseudomonas aeruginosa , and Candida albicans , by using the agar well diffusion method, performed in triplicate. The extract exhibited inhibitory effects, with the most pronounced activity observed against Staphylococcus aureus (mean zone of inhibition: 18.6 ± 0.05 mm). The minimum inhibitory concentration (MIC) was determined using the broth microdilution method, revealing MIC values of 25 mg/ml for S. aureus and C. albicans , 50 mg/ml for E. coli , and 100 mg/ml for P. aeruginosa . This study has several limitations, including the absence of positive controls (e.g., standard antibiotics), lack of cytotoxicity assessment, preliminary nature of qualitative phytochemical analysis, and the need for  in vivo  validation. Therefore, these findings should be interpreted as preliminary screening results that require further confirmation using more rigorous experimental designs.